Hybrid niobium and titanium nitride nanotube arrays implanted with nanosized amorphous rhenium–nickel: An advanced catalyst electrode for hydrogen evolution reactions. (28th February 2020) - Zhang, Huibin; Chen, Xuanhan; Lin, Zhimao; Zhang, Liqiang; Cao, Huazhen; Yu, Linping; Zheng, Guoqu
Abstract: The scalable application of high-performance electrocatalysts with fine nanostructures for hydrogen evolution reactions (HER) depends on the development of durable and active electrode supports. Transition metal nitrides are considered as candidates due to their high conductivity, favorable catalytic activity, and excellent chemical stability in acidic or alkaline aqueous solutions. The present work proposed to fabricate self-ordered hybrid niobium–titanium (Nb–Ti) nitride nanotube arrays (NNAs) on Nb–Ti alloy panels by an anodization and subsequent nitridation process. Results showed that the highly ordered NNA is composed of mixed Nb4 N5 and TiN and has merits of super hydrophilicity, outstanding corrosion resistance, and high conductivity. On the basis of the successful synthesis of Nb–Ti NNA, the nano–sized amorphous rhenium–nickel (Re–Ni) alloy was electrodeposited onto the NNA support, forming the Re–Ni/NNA composite electrode. Electrochemical tests exhibited that the Re–Ni/NNA composite electrode can provide a current density of 50 mA cm −2 in 1.0 M KOH at a potential of −0.18 V vs. RHE and maintain stability in a testing period of 100 h. This superior HER performance is attributed to the combination of Re–Ni particles and Nb–Ti NNA support, which can benefit the diminution of charge transfer resistance and the improvement of catalytic activity. Graphical abstract: Image 1 Highlights: Hybrid Nb–Ti nitride nanotube arrays were prepared by an anodizing-nitriding process. Highly ordered Nb–Ti nitride nanotube arrays were composed of mixed Nb4 N5 and TiN. Nano-sized amorphous Re–Ni alloy was electrodeposited on the Nb–Ti NNA support. Re–Ni/NNA composite electrode showed a high electrocatalytic activity towards HER. Re–Ni/NNA composite electrode maintained stable in a testing period of 100 h.